Inhibition of Salmonella sp. Growth in Comparison with Antibiotics and Pineapple (Ananas comosus) Squeeze - Masda Admi; Erina Erina; Azhari Azhari; Ummu Balqis; Muhammad Hambal; Darmawi Darmawi (Syiah Kuala University, 2015)
The purpouse of this study to examine antibiotics inhibition growth of Salmonella sp. isolated from feces of broiler chickens to chloramphenicol, gentamicin, and tetracycline in coparison with pineapple squeeze. Swab sample from broiler chicken cloaca was cultured to nutrient broth media and incubated at 37°C temperature for 24 hours. Culture was compared with Mc Farland 3 standardization, and separated on surface of Muller Hinton Agar (MHA). Antibiotic sensitivity was tested by mean of chloramphenicol, gentamisin, and tetrasiklin in coparison with pineapple squeeze. The antibiotic disks (Oxoid) were put on the surface of MHA media which had inoculated with Salmonella sp. bacteria. Antibiotic sensitivity was determined based on formation of inhibition zone in surrounding of antibiotic disc. The result showed that Salmonella sp. bacteria growth was inhibited in ≥ 21 mm and ≥ 18 mm, ≥ 7 mm and ≥ 9 mm against chloramphenicol, gentamisin, tetrasiklin, and pineapple squeeze respectively. This research concluded that the Salmonella sp. cultured in this manner were sensitive to chloramphenicol and gentamisin. The inhibition growth of Salmonella sp. caused by chloramphenicol and gentamicin was significantly higher in comparison with pineapple (Ananas comosus) squeeze, meanwhile the Salmonella sp. bacteria was resistance against tetracycline. Our result suggest that both antibiotics chloramphenicol and gentamicin were recommended for antibiotic therapy in Salmonella sp. infection.